Air Pollution around Schools and Poorer Student Health and Academic Performance: A Case of Dhaka, Bangladesh - Jahan, Nusrat (ABC Journal of Advanced Research, 2020)
Dhaka is one of the most vulnerable cities of the world to the adverse effects of air pollution and variables. Children of Dhaka are the most affected group of people to any crucial change in any climatic change, i.e., air pollution. Exposing children to any environmental pollutants during the times of their growth can lead to long-lasting health problems, dysfunction, and disease. The location of the schools can increase their exposure. In such, a survey has been conducted on the extent of air pollution from industrial sources around different schools in Dhaka to find out whether air pollution threatens children’s health and academic success. We found that schools in the highest air polluted areas had the poorer attendance rate — indicates poor health—and the highest proportions of students who are not performing up to their potential in educational testing standards. However, Dhaka and some other cities do not require officials considering a site for a new school to analyze its air quality. The survey result shows that such requirements are needed. For schools already in existence, we recommend that their environmental quality should be examined and improved to save our future generation.